Rates of and Risk Factors for Trabecular and Cortical BMD Loss in Middle‐Aged and Elderly African‐Ancestry Men. (16th February 2015) - Sheu, Yahtyng; Bunker, Clareann H; Jonnalagadda, Pallavi; Cvejkus, Ryan K; Patrick, Alan L; Wheeler, Victor W; Gordon, Christopher L; Zmuda, Joseph M
ABSTRACT: Low trabecular (Tb) and cortical (Ct) volumetric BMD (vBMD) are related to increased fracture risk, but little is known about the patterns and correlates of Tb and Ct vBMD loss with aging. We examined the rates of change in total, Tb.vBMD, and Ct.vBMD at the radius and tibia, and identified factors associated with vBMD loss among 1569 men of African descent aged 40 years and older. Quantitative computed tomography was used to measure vBMD 6 years apart. The annualized rate of loss in Tb.vBMD was significant at the radius (–0.047%/yr, p = 0.016) but not at the tibia. At the radius, a significant loss of Tb.vBMD was observed in men aged 40 to 49 years that appeared to be attenuated and not statistically significant among older age men. In contrast, the decline in Ct.vBMD was similar at both skeletal sites (–0.254 to –0.264%/yr, p < 0.0001) and was consistent across all age groups. Positive associations were found for vBMD changes with body weight (all but radius Ct.vBMD) and diabetes (Ct.vBMD only), whereas negative associations were found with hypertension (all but radius Tb.vBMD), smoking (Ct.vBMD only), and androgen deprivation therapy (cortical vBMD only). Trabecular and cortical vBMD loss appears to follow different patterns among middle‐ and older‐aged men of African ancestry. Factors associated with the decline in vBMD also varied by compartment and anatomical site. Additional studies are needed to better understand the physiological mechanisms underlying early BMD loss among African‐ancestry men. © 2014 American Society for Bone and Mineral Research.